The Quaternary Stratigraphy of a Section of the Sibowe River, South-West Swaziland - Ampe, Carole; Van Regenmortel, Gunter (Afrika Focus, 1991)
In south-west Swaziland a river terrace along the Sibowe river is formed by active river incision. A complex profile along this terrace showing alluvial and colluvial deposits reflecting changes in environmental conditions since at least the last 30 000 years is exposed. Examination of soil characteristics, relative position of the composite strata as well as river dynamics leads to a stratigraphie interpretation which has been fitted into a time frame. The basal gravel, alluvial in nature, dates from before the deposition of the Mphunga colluvium which has been deposited between 30 300 and 8490 before present. On the colluvium occurs an alluvium most probably deposited during the Early Holocene. The incision of the terrace to its present level has occurred during the Late Holocene. KEY WORDS: buried soil, colluvium, degradation, gravel deposits, lateral erosion, Swaziland